Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965-2012: Land use planning area Herstadberg - Swedish National Heritage Board, UV Öst (Uppsala University, 2018)
The information in the abstract is translated from the archaeological report:
In connection with local planning concerning an extension of the golf course in Herstadberg and Loddby, Norrköping municipality wished to elucidate the archaeological conditions in the area. A archaeological assessment (phase 1) has been performed by the Swedish National Heritage Board's Contract Archaeology Service, UV Öst. The assessment has shown that the development will affect an area of regional, cultural interest, as well as the oldest locations of the manor Herstadberg and the village Loddby, a brickworks remnant, three building remnants, a historically interesting building, five prehistoric graves and six topographically delimited areas which are likely to contain unmarked archaeological remains. A expansion of the golf course would affect Loddby to a higher degree than Herstadberg, since the latter is already much affected by the residential area, the railway and the motorway.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the archaeological assessment (phase 1) was to present all visible archaeological and cultural remains within the survey area, and to point out areas where unmarked remains were likely to be found. The aim of the assessment was to present an overview of the area's history, character and preserved archaeological remains, to suggest further archaeological measures, to describe how the area would be affected by the planned development and to serve as a basis for future decisions regarding the area, made by the County Administrative Board.

The ZIP file consists of shapefiles and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
I samband med pågående detaljplaneprogramarbete inför planerad utökning av golfbana inom Herstadberg och Loddby önskar Norrköpings kommun att klargöra de arkeologiska förutsättningarna. En arkeologisk utredning, etapp 1, har utförts av Riksantikvarieämbetet UV Öst. Efter genomförd utredning konstaterades att ett regionalt intresseområde för kulturmiljö berörs. Vidare berörs både Loddbys och Herstadbergs äldsta tomter, en tegelbrukslämning, tre bebyggelselämningar, en kulturhistoriskt intressant byggnad, fem förhistoriska gravar samt sex topografiskt avgränsade områden som bedöms innehålla ovan mark omarkerade lagskyddade fornlämningar. En utbyggnad av golfbanan skulle påverka Loddbyområdet i högre grad än Herstadområdet, därför att bruksmiljön (Herstadområdet) redan har påverkats starkt av villabebyggelse, järnvägen och motorvägen och skulle tappa karaktär ytterligare om en golfbana placerades tätt inpå miljön.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
En utredning etapp 1 syftar till att redovisa samtliga synliga forn- och kulturlämningar och anvisa områden där sannolikheten för ovan mark omarkerade fornlämningar bedöms vara stor. Syftet med utredningen var att ge en översiktlig bild av områdets historia, karaktärsdrag och kvarvarande lämningar från de betydelsebärande epokerna, vid behov ge förslag på fortsatta arkeologiska åtgärder, beskriva hur områdets värden skulle påverkas av en exploatering enligt planförslaget samt tillhandahålla ett underlag som Länsstyrelsen i senare skede kan utgå ifrån för att kunna besluta om eventuella fortsatta arkeologiska insatser enligt Kulturminneslagen.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Planprogramområde Herstadberg
Keywords: historical period; historisk tid; Modern age; nyare tid; prehistoric time; förhistorisk tid; HISTORY; HISTORIA; Archaeology; Arkeologi